Territory Brand: Approaches to Definition, Simulation Methodology - POBIRCHENKO, Viktoriya; SHUTAIEVA, Elena; KARLOVA, Anna; POLYUKHOVICH, Elena (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019, 2019)
Taking into account the specifics of modern geo-economic development, territorial branding plays the role of the basis for territorial management. Territorial branding is aimed at generating the competitive advantages of a particular territory, at improving its image, popularity, and reputation of goods and services produced in a given territory in the eyes of consumers. The analysis of the currently existing approaches to the understanding of the essence of the notion of “territory brand” and the essence of branding in general are given in this article, and also the features and constituent elements of foreign and Russian models of a territorial brand are revealed. This ultimately allowed the authors to clarify the concept of this definition. According to the authors, a territory brand is a combination of unique qualities, unfading universal values reflecting the originality, unique original consumer characteristics of this territory and community, widely known, received public recognition and enjoying strong demand among the consumers of the territory, contributing to the formation of preferences of this territory over others in a situation of choice. The brand is presented by the authors of the article as the most important way to realize the competitive advantages of a territory, a tool for competitiveness, differentiation, and uniqueness. Simulation is used as a research method. It became possible to clarify theoretically the essence of the concept of “territory brand” and systematically comprehend the territorial branding technology by building the author’s model for the territory brand.